Management and Production of Banana Stem Chips as an Alternative Business and Local Product Innovation in Merjosari - S. Candra Hastuti; Windy Wahju Purnomo (Talenta Publisher, 2026)
Merjosari Village, Malang City, boasts abundant natural resources in the form of banana plantations. After the fruit is harvested, banana stems (